Functional comparison of phosphomimetic S15D and T160D mutants of myosin regulatory light chain exchanged in cardiac muscle preparations of HCM and WT mice - Kazmierczak, Katarzyna; Liang, Jingsheng; Gomez-Guevara, Michelle; Szczesna-Cordary, Danuta (Frontiers in Cardiovascular Medicine, 2022)
In this study, we investigated the rescue potential of two phosphomimetic mutants of the myosin regulatory light chain (RLC, MYL2 gene), S15D, and T160D RLCs. S15D-RLC mimics phosphorylation of the established serine-15 site of the human cardiac RLC. T160D-RLC mimics the phosphorylation of threonine-160, identified by computational analysis as a high-score phosphorylation site of myosin RLC. Cardiac myosin and left ventricular papillary muscle (LVPM) fibers were isolated from a previously generated model of hypertrophic cardiomyopathy (HCM), Tg-R58Q, and Tg-wild-type (WT) mice. Muscle specimens were first depleted of endogenous RLC and then reconstituted with recombinant human cardiac S15D and T160D phosphomimetic RLCs. Preparations reconstituted with recombinant human cardiac WT-RLC and R58Q-RLC served as controls. Mouse myosins were then tested for the actin-activated myosin ATPase activity and LVPM fibers for the steady-state force development and Ca2+-sensitivity of force. The data showed that S15D-RLC significantly increased myosin ATPase activity compared with T160D-RLC or WT-RLC reconstituted preparations. The two S15D and T160D phosphomimetic RLCs were able to rescue Vmax of Tg-R58Q myosin reconstituted with recombinant R58Q-RLC, but the effect of S15D-RLC was more pronounced than T160D-RLC. Low tension observed for R58Q-RLC reconstituted LVPM from Tg-R58Q mice was equally rescued by both phosphomimetic RLCs. In the HCM Tg-R58Q myocardium, the S15D-RLC caused a shift from the super-relaxed (SRX) state to the disordered relaxed (DRX) state, and the number of heads readily available to interact with actin and produce force was increased. At the same time, T160D-RLC stabilized the SRX state at a level similar to R58Q-RLC reconstituted fibers. We report here on the functional superiority of the established S15 phospho-site of the human cardiac RLC vs. C-terminus T160-RLC, with S15D-RLC showing therapeutic potential in mitigating a non-canonical HCM behavior underlined by hypocontractile behavior of Tg-R58Q myocardium.